THE VALUE OF URINARY CYTOLOGY AND HYDRONEPHROSIS TO PREDICT MUSCLE INVASIVE BLADDER CANCER - ardiansyah, ferdi; Danarto, H R (Indonesian Urological Association, 2016)
Objective: We evaluated the value of urinary cytology, and presence of hydronephrosis to predict muscle invasive bladder cancer. Material & methods: We retrospectively analyzed data of 167 patients that diagnosed bladder cancer from medical record at Sardjito General Hospital Yogyakarta, between 2004-2011. Preoperative parameters were evaluated including age, gender, number and location of bladder cancer, urinary cytology, as well as presence of hydronephrosis. The outcome was muscle invasive bladder cancer. Results: A total of 96 (57.5%) patients had positive urinary cytology, 80 (47.9%) had hydronephrosis, most location of tumor were in trigone 43 (25.7%). The youngest patient was 26 years and the oldest was 84 years old, male was most affected in 145 (86.8%). On bivariate analysis, positive urinary cytology and hydronephrosis were associated with muscle invasive bladder cancer (OR 0.08 CI 0.038–0.167; OR 30.24 CI 12.72–71.89, respectively, each p < 0.05). Combination urinary cytology and hydronephrosis incrementally improved prediction of muscle invasive bladder cancer with positive and negative predictive value were 93.9% and 71.4%, respectively. Presence of hydronephrosis was associated with tumor location in trigone (p < 0.05). Conclusion: Urinary cytology and hydronephrosis were associated with muscle invasive bladder cancer, and can be used to predict muscle invasive bladder cancer.